Serum concentration of sFas and sFasL in healthy HBsAg carriers, chronic viral hepatitis B and C patients - Lapinski, Tadeusz Wojciech (World J Gastroenterol, 2004)
AIM: To estimate the amount of apoptosis among healthy HBsAg carriers, patients with chronic HBV infection treated with lamivudine and patients with chronic HCV infection treated with interferon alpha and ribavirin. Activity of apoptosis was evaluated by serum sFas/sFasL concentration measurement. Moreover dependence between apoptosis and HBV-DNA or HCV-RNA levels was studied. METHODS: Eighty-six persons were included into study: 34 healthy HBsAg carriers, 33 patients with chronic HBV infection and 19 patients with chronic HCV infection. Serum levels of sFas/sFasL were measured by ELISA assay. HBV-DNA and HCV-RNA were measured by RT-PCR assay. Levels of sFas/sFasL were determined before and 2 and 12 wk after therapy in patients with chronic hepatitis B and C infection. HBV-DNA or HCV-RNA was detected before treatment and 6 mo after treatment. RESULTS: Twenty-four (71%) healthy HBsAg carriers showed HBV-DNA over 10(5)/mL, which was comparable to the patients with chronic hepatitis B. Independently from HBV-DNA levels, the concentration of sFas among healthy HBsAg carriers was comparable to healthy persons. Among patients with chronic hepatitis B and C, the concentration of sFas was significantly higher in comparison to healthy HBsAg carriers and healthy persons. In chronic hepatitis B patients the concentration of sFas was decreased during lamivudine treatment. Among chronic hepatitis C patients the concentration of sFas was increased during IFN alpha and ribavirin treatment. sFasL was not detected in control group. Furthermore sFasL occurred more frequently in chronic hepatitis C patients in comparison to chronic hepatitis B patients. CONCLUSION: There are no correlations between apoptosis and HBV-DNA levels. However ther is an association between apoptosis and activity of inflammation in patients with chronic HBV infection. Apoptosis can be increased in patients with chronic hepatitis C by effective treatment which may be a result of apoptosis stimulation by IFN-α.